PENYULUHAN HIPERGLIKEMIA DAN HIPERKOLESTEROLEMIA DI MASYARAKAT MUARA FAJAR PEKANBARU - Alfi Budiman; Fahrani Eka Astuti; Elizabeth W. Theresia; Sarah Ester Priskila (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
Lifestyle changes can reduce health status in the community. Lack of public knowledge regarding the importance of maintaining glucose and cholesterol levels will lead to an increased risk of degenerative diseases. Supporting laboratories for early detection of degenerative diseases include examination of glucose and cholesterol. These examinations can help in preventing and early treatment to prevent degenerative diseases. This community service aimed to provide health education, conduct examinations related to hypercholesterolemia and hyperglycemia in the people of Muara Fajar Pekanbaru. Community service begin with problem analysis, preparation of proposals, implementation of activities. The community service was attended by 30 participants. The results of the examination were 23 participants had cholesterol levels 200 md/dL and 21 participants had glucose levels 200 md/dL. Based on the results of filling out the questionnaire, most people do not understand the dangers of hypercholesterolemia and hyperglycemia. Based on the results of filling out the questionnaire, most people do not understand the dangers of hypercholesterolemia and hyperglycemia. Counseling on the dangers of hypercholesterolemia and hyperglycemia given to the public was very useful. The public can understand the causes, signs, symptoms and risk factors of hypercholesterolemia and hyperglycemia.Keywords:Cholesterol, Hypercholesterolemia, Glucose, Hyperglycemia